Development of Higher Order Thinking Skills Through Project-Based Learning Methods: Pengembangan Keterampilan Berpikir Tingkat Tinggi Melalui Metode Pembelajaran Berbasis Proyek - Tambak, Syahraini; Siregar, Rahmayani (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study was to analyze the effect of the project-based learning model on the high-level thinking skills of students of the Islamic Religious Education Study Program, Islamic University of Riau. This type of research is quantitative with a correlation approach. This study involved 259 samples. Data collection techniques using questionnaires, documentation and data analysis techniques using normality tests, descriptive and simple linear regression. The results showed that the level of mastery of the project-based learning model in student perceptions and students' higher-order thinking skills was in the high category. significance 0.000. The big influence is moderate (0.440 or 44%). The Project-based learning model influences the high-level thinking skills of students of the Islamic Religious Education Study Program at the Islamic University of Riau. This research has implications for the theory of higher order thinking skills in Islamic Higher Education.